2007
DOI: 10.1021/jp064480d
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectra, DFT Calculations, Unusual Structure, Anomalous CH2 Wagging and Twisting Modes, and Phase-Dependent Conformation of 1,3-Disilacyclobutane

Abstract: Our previously published infrared and Raman spectra of 1,3-disilacyclobutane (13DSCB) and its 1,1,3,3-d4 isotopomer have been reexamined and partially reassigned on the basis of DFT and ab initio calculations. The calculations confirm previous microwave work that the CSiC angles in the ring are unexpectedly larger than the SiCSi angles. This may arise from the partial charges on the ring atoms. The calculations are in excellent agreement with the observed spectra in both frequency and intensity. They also demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…the presence of the hydrated water in these samples. For molecular systems which we have studied previously [17][18][19][20][21][22][23][24][25][26][27] we typically have found remarkably good agreement between the observed and calculated spectra. Here, however, there are significant differences which can be attributed to the intermolecular hydrogen bonding.…”
Section: Vibrational Modessupporting
confidence: 61%
“…the presence of the hydrated water in these samples. For molecular systems which we have studied previously [17][18][19][20][21][22][23][24][25][26][27] we typically have found remarkably good agreement between the observed and calculated spectra. Here, however, there are significant differences which can be attributed to the intermolecular hydrogen bonding.…”
Section: Vibrational Modessupporting
confidence: 61%
“…24,35 In this work, the geometry optimization and vibration frequencies of the reactants, products, and intermediates for each reaction were calculated using MP2 with the 6-311++G(d,p) basis set. The frozen core approximation was employed in all geometry optimizations.…”
Section: ■ Theoretical Methodsmentioning
confidence: 99%
“…Previous studies [19,25,32,33] have shown that calculations using the second-order Möller-Plesset (MP2) perturbation theory does an excellent job in predicting the structures of silacylcobutane molecules. Therefore, the geometric structures of the six molecules mentioned above were optimized at the MP2 level of theory with the 6-311++G(d,p) basis set.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Various experimental methods including microwave spectroscopy [17][18][19], infrared/ Raman spectroscopy [20][21][22][23][24][25], and gas electron diffraction [26][27][28][29][30] have been employed to elucidate the geometric structures of silacyclobutane and its substituted derivatives. At the same time, theoretical calculations of a variety of such molecules as silacyclobutane (SCB) [30][31][32], 1-methyl-1-silacyclobutane (MSCB) [25], 1,1-dimethyl-1-silacycolbutane (DMSCB) [27], 1,3-disilacyclobutane (DSCB) [33], and 1,1,3,3-tetramethyl-1,3-disilacyclobutane (TMDSCB) [28] have been reported in the literatures. In a recent study of the structures of silacyclobutane and its 1,1-dicholoro and 1,1-difluoro derivatives using ab initio calculations [32], AlSaadi and Laane have shown that the dihedral angles of puckering decreased in the two 1,1-disubstituted derivatives of SCB as a result of increasing electronegativity of the substituent.…”
Section: Introductionmentioning
confidence: 99%